RUU KEPOLISIAN: TELAAH TERHADAP PERLINDUNGAN POLISI WANITA PERSPEKTIF TEORI KEADILAN BERMARTABAT - Rizky Karo Karo (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2025)
One of the considerations for the formation of the Draft Law on the Indonesian National Police (RUU Kepolisian) is to adapt to the dynamics, developing legal needs in society, and the state's constitutional life. In this paper, the author discusses and analyzes the RUU Kepolisian in providing legal protection for female police officers. The research problem raised is: what is the ideal regulation for the legal protection of female police officers in the RUU Kepolisian? The research method used is normative-juridical, using a qualitative approach by analyzing primary, secondary, and tertiary legal materials. The conclusion of the research is that the RUU Kepolisian should specifically regulate the legal protection of female police officers in carrying out their duties, and the RUU Kepolisian can refer to relevant laws on legal protection, such as Law No. 39 of 1999 on Human Rights (UU HAM). Such protection is solely aimed at humanizing humans, humanizing female police officers as the goal of the theory of dignified justice